Particle-in-Cell with Monte Carlo Collisions Gun Code Simulations of a Surface-Conversion H^− Ion Source (Communications in Computational Physics, 2008)
We present an extended update on the status of a particle-in-cell with MonteCarlo collisions (PIC-MCC) gun code developed at Los Alamos for the study of surface-converter H− ion sources. The program is fully kinetic. Some of the program's featuresinclude: solution of arbitrary electrostatic and magnetostatic fields in an axisymmetric(r,z) geometry to describe the self-consistent time evolution of a plasma; simulationof a multi-species (e−, H+, H2+ , H3+, H−) plasma discharge from a neutral hydrogengas and filament-originated seed electrons; full 2-dimensional (r,z) 3-velocity (vr, vz,vφ) dynamics for all species; detailed collision physics between charged particles andneutrals and the ability to represent multiple smooth (not stair-stepped) electrodes ofarbitrary shape and voltage whose surfaces may be secondary-particle emitters (H−and e−). The status of this development is discussed in terms of its physics contentand current implementation details.